Synthesis and characterization of Ti-doped MgMn2O4 cathode material for magnesium ion batteries - Zainol, Nurul Husna; Hambali, D.; Osman, Zurina; Kamarulzaman, Norlida; Rusdi, Roshidah (Springer Verlag (Germany), 2019)
Magnesium batteries demonstrate potential candidate for next-generation energy storage devices because of their high energy density and low raw-materials costs. In comparison with lithium, magnesium is inherently much safer due to its air stable and environmental friendly. In the present work, magnesium manganese oxide (MgMn 2 O 4 ) with Ti-doped was synthesized by a self-propagating combustion method using citric acid as a reducing agent. The precursors of MgMn 2 O 4 and MgMn (2-x) Ti x O 4 , (x = 0.1) were annealed at 700 °C for 24 h. The prepared samples were further characterized by using Simultaneous Thermal Analysis (STA), X-ray diffraction (XRD), and Field Emission Scanning Electron Microscopy (FESEM). Then, the optimized sample was used as cathode in magnesium ion battery using polymer-based electrolyte. The charge-discharge profile of the fabricated battery was discussed.